INDUKSI MUTASI RADIASI SINAR GAMMAPADA BEBERAPA VARIETAS KEDELAI HITAM (Glycine max (L.) Merrill) - Kurnia Ramadani Purba1 Ramadani Purba; Eva Bayu Bayu; Isman Nuriadi (Jurnal Agroekoteknologi, 2013)
This study aimed to get the genetic diversity some varieties of black soybeans due to the influence of gamma rays. Research was conducted at Balai Benih Induk Tanaman Palawija, Deli Serdang (+ 25 m above sea level)  from April - August 2012 used randomized block design. The first factor is the radiation doses with 4 level are 0, 10, 15, and 20 krad  and the second factor is three varieties are Detam-1, Detam-2, and Cikuray. The treatment was repeated three times. The results showed that radiation significant of percentage of germination,  plant height at 4-5 week after plant and harvest time. Varieties significant of plant height at 2-5 week after plant, flowering time, harvest time, number of empty pods, seed weight per sample, weight of 100 seeds, but not significant of the number of productive branch and number of pod contain. Whereas, interaction between radiation and varieties only significant of plant height at 4 week after plant. Coefficient variability genotipe values ranged between 0,39 – 17,85 and coefficient variability fenotipe values ranged between 1,21 – 18,76. Heritability values ​​ranged between 0,10 - 0,96. Research should be continued so know production of varieties which are higher.   Keyword: black soybeans, radiation, varieties